PENENTUAN KEBERHASILAN PETERNAKAN AYAM DENGAN PENDEKATAN INDEKS PERFORMA BERBASIS MOBILE PADA PETERNAKAN KARANG INDAH - Norfajriyah, Norfajriyah; Zaky, Umar (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Broiler chicken farming plays an important role in meeting the demand for chicken meat in Indonesia, with chicken meat consumption reaching 8.0 kg/capita/year in 2022, which is known to have increased by 6.67% from 2021. The rise in consumption drives farmers to increase productivity through daily record-keeping, resulting in a performance index to measure the success of the farm over one period. However, manual record-keeping at Karang Indah farm often leads to data loss and inaccurate performance index calculations. Based on the owner's needs, a mobile-based record-keeping system is required, designed using Kotlin and Laravel, and integrating a REST API via Retrofit2. The development process of this system follows the waterfall method, starting with analysis, design, implementation, testing, and maintenance. This system enables the recording of chicken entries, development, health, feed, sales, and education, and can automatically calculate the performance index. The system is accessible via Android, with more comprehensive record results available through the website, improving the efficiency and accuracy of the farm's performance index calculations. The performance index has five categories: <300 (poor), 301-325 (fair), 326-350 (good), 351-400 (very good), and >400 (excellent).